Agricultural technologies adoption and smallholder farmers' welfare: Evidence from Northern Ghana - Abdulai Adams; Emmanuel Tetteh Jumpah (Cogent Economics & Finance, 2021)
Improving the welfare of smallholder farmers through the introduction of improved technologies has gained increased attention in recent times. The focus now transcends the mere development and introduction of these farming technologies to improve productivity alone. Policymakers, particularly those in developing countries now pursue the implementation of interventions that promote the use of improved technologies to advance the welfare of smallholder farmers. However, the impact of such intervention to inform future policy decisions remains largely lacking and under theorized. The current study, therefore, analysed the impact of technology adoption on smallholder farmers' welfare. We obtained data from 461 technology adopters and non-adopters by using purposive and simple random sampling. Using the propensity score matching technique, we estimated the impact of technology adoption on smallholder farm households. The results show that regional location, educational level, age, and Farmer Base Organisation (FBO) membership are the main determinants of technology adoption among smallholder farmers. Technology adoption had a positive but statistically insignificant impact on welfare. Consumption and clothing expenditure increased with adoption but not healthcare. To improve the impact of technology adoption on smallholder farmer welfare, emphasis should be placed on business supporting/advisory services; agricultural extension outreach, finance/input support among others.
Keywords: 330; clothing and healthcare expenditure; consumption; smallholder farmers; Technology; welfare